Specific inflammatory profile of acute ischemic stroke patients with left atrial enlargement - Fontaine, Julia; Leboube, Simon; Bochaton, Thomas; Thibault, Hélène; Amaz, Camille; Cho, Tae-Hee; Paccalet, Alexandre; Crola Da Silva, Claire; Duhamel, Suzanne; Buisson, Marielle; Rascle, Lucie; Bidaux, Gabriel; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: The inflammatory process underlying atrial myopathy may affect the inflammatory response activated in acute ischemic stroke (AIS). Objectives: We aimed to assess whether left atrial enlargement (LAE) as a marker of atrial myopathy is associated with a different profile of circulating inflammatory markers in AIS patients. Methods: HIBISCUS-STROKE is a cohort study including anterior circulation AIS patients treated with mechanical thrombectomy following MRI. 10 circulating inflammatory markers were measured at admission and 6, 24 and 48 hours from admission. LAE was defined as left atrial volume index (LAVi) ≥ 34 ml/m2. A multiple logistic regression model was performed to detect an independent association between area under the curve (AUC) of these markers and LAE. Results: We included 143 patients. Of them 85 (59.4%) patients had LAE. On univariable analysis, patients with LAE had higher soluble form suppression of tumorigenicity 2 (sST2), soluble tumor necrosis factor receptor I (sTNFR1) and vascular cellular adhesion molecule-1 (VCAM-1) AUC, were older, more often female, had a higher national institute of health stroke score (NIHSS) and blood glucose level at admission, had more often hypertension, and a cardioembolic source of AIS such as atrial fibrillation while they were less often current smoker and had a lower rate of tandem occlusion than patients without LAE. On multivariable analysis, among circulating inflammatory markers only high VCAM-1 (OR 9.13, 95%CI 3.21-25.9) and sST2 (OR 3.40, 95%CI 1.68-6.86) AUC remained associated with LAE. Conclusions: High VCAM-1 and sST2 levels within the first 48 hours are associated with LAE in AIS patients.